Pharmacoeconomic analysis of treatment with nilotinib as the second line therapy in patients with chronic myeloid leukemia - N. A. Avxentyev; M. Yu. Frolov; A. S. Makarov (IRBIS LLC, 2018)
Ilmatinib is currently the most widely used tyrosine kinase inhibitor for the treatment of chronic myeloid leukemia (CML) in Russia. When patients develop resistance or intolerance to imatinib, second generation tyrosine kinase inhibitors (Tkis) are used. in Russia, nilotinib, dasatinib and bosutinib are registered in second-line, however only dasatinib is included in the government drug reimbursement program.The aim of this study was to conduct a pharmacoeconomic comparison of nilotinib, dasatinib and bosutinib as second-line treatments for patients with CML from the Russian healthcare system perspective.Materials and methods. Using the clinical trial data we developed a Markov model of CML progression on nilotinib, dasatinib or bosutinib second-line therapy and calculated the medical costs per patient. Both costeffectiveness analysis and budget-impact analysis reflected the local practice and the drug reimbursement approval process.Results. The average medical cost (per year) for nilotinib (1 683 thousand rubles or US$27 075) was 8.4% lower than that for dasatinib and 35.2% lower than for bosutinib. The 4-year total medical cost of treatment with nilotinib was 4 372 thousand rubles (US$ 70 336), which was 13.9% lower compared to dasatinib and 37.3% lower compared to bosutinib. nilotinib also had a lower cost/effectiveness ratio (US$ 1 602, 1 910 and 2 537 per life month for nilotinib, dasatinib and bosutinib, respectively). The estimated number of patients in Russia who need second-line treatment for CML is 996 patients. if nilotinib were included in the Government Reimbursement Program, a saving of 771 million rubles (US$ 12,4 million) over four years would be reached.Conclusions. When compared with dasatinib or bosutinib, nilotinib is the cost-saving option for the second-line treatment of CML patients in Russia.